Strategi Penginjilan Barnabas dan Saulus dalam Kisah Para Rasul 13:4-12 - Tutur Parade Tua Panjaitan (Sekolah Tinggi Teologi Sumatera Utara, 2022)
This research was conducted to determine the evangelistic strategies of Barnabas and Saul in Acts 13:4-12. Evangelism is an important topic in Christianity, given the duty the Jesus Christ left to his disciples in particular and to the church in general as written in the Bible. In principle, the gospel must be preached in order for people to believe. What was the evangelistic strategy of Barnabas and Saul in Acts 13:4-12? Using the exegesis or inductive method, the author worked on this study, after first observing the verses, then drawing conclusions based on the data and facts of the Bible found. According to church tradition, the author of Acts is the same as the author of luke's gospel, Luke. The background of verses is outlined in Acts 12:24-25 that the Gospel was preached to many people, then from Jerusalem Barnabas and Saul returned to Antioch, after completing the preaching of the Gospel. The context of this verses is the state of the Antiochian church which already had several ministers, namely prophets and teachers. The Holy Ghost commissioned Barnabas and Saul to spread the gospel. Eventually the Antiochian church released Barnabas and Saul to become missionaries, out of obedience to the commandments of the Holy Spirit. The evangelism strategies of Barnabas and Saul are: evangelism traveling to the cities, evangelism starting from those closest to you, evangelism in houses of worship, evangelism in private.AbstrakPenelitian ini dikerjakan untuk mengetahui strategi penginjilan Barnabas dan Saulus dalam Kisah Para Rasul 13:4-12. Penginjilan merupakan topik yang penting dalam kekristenan, mengingat tugas yang ditinggalkan Yesus Kristus kepada murid-muridNya pada khususnya dan kepada gereja pada umumnya sebagaimana tertulis dalam Alkitab. Pada prinsipnya, Injil harus diberitakan agar orang menjadi percaya. Bagaimanakah strategi penginjilan Barnabas dan Saulus dalam Kisah Para Rasul 13:4-12? Dengan metode eksegese atau induktif, penulis mengerjakan penelitian ini, setelah terlebih dahulu mengamati nas, kemudian menarik kesimpulan berdasarkan data dan fakta Alkitab yang ditemukan. Menurut tradisi gereja, penulis Kisah Para Rasul sama dengan penulis Injil Lukas yaitu Lukas. Latar belakang nas diuraikan dalam Kisah Para Rasul 12:24-25 bahwa Injil diberitakan kepada banyak orang, kemudian dari Yerusalem Barnabas dan Saulus pulang ke Antiokhia, setelah menyelesaikan pengabaran Injil. Konteks nas ini adalah keadaan jemaat Antiokhia yang sudah memiliki beberapa pelayan, yakni nabi dan pengajar. Roh Kudus menugaskan Barnabas dan Saulus untuk menyebarkan Injil. Akhirnya jemaat Antiokhia melepaskan Barnabas dan Saulus untuk menjadi misionaris, karena taat kepada perintah Roh Kudus. Strategi penginjilan Barnabas dan Saulus adalah: penginjilan keliling ke kota-kota, penginjilan dimulai dari orang-orang terdekat, penginjilan di rumah ibadah, penginjilan secara pribadi.